Genetic and Molecular Biology Implications in the Surgical Treatment of Gastric Cancer - Roberto Eduardo Aguirre Fernández; Miguel Ángel Serra Valdés (Revista Finlay)
Gastric cancer is one of the leading causes of death from neoplasms in the world. Current clinical practice guidelines offer treatment models that involve surgery, radiotherapy, chemotherapy, immunotherapy and therapy directed at specific growth receptors, however, genetic and molecular biology aspects are not always taken into account in medical practice. The objective of this review is to articulate the most relevant current aspects of genetics and molecular biology in relation to gastric cancer, to integrate them into the clinical guidelines of patients and relatives with the diagnosis or at risk of suffering from this type of neoplasia. For them, genetic advances and syndromes related to gastric cancer, molecular classifications and implications in their management were reviewed. The databases Google Scholar, Elsevier, and PubMed were used in the last 10 years, selecting the most important full-text from a qualitative point of view. The integration of personal and family history with genetic elements needs to be taken into account in the diagnostic management and prevention of this disease. The inclusion of genetic and molecular elements in all clinical practice guidelines is suggested.